Efficacy of Chitosan Irrigation for Pulpectomy in Non-Vital Primary Teeth: A Clinical-Radiographic Study - Mossad , Zeina M.; Zakaria, Amira M.; El-Baz, Ghada A.; M. Farag, Mohamed Sherif (Journal of Neonatal Surgery, 2025)
Introduction: Despite the antibacterial properties of sodium hypochlorite (NaOCl), it is cytotoxic and cannot effectively remove the smear layer. Chitosan is a natural nontoxic biopolymer having antimicrobial properties. Aim: Clinical and radiographic assessment of 0.2% chitosan as final irrigating solution in pulpectomy in non-vital primary teeth for 1 and 3 minutes versus sodium hypochlorite. Methods: A randomized clinical trial included 45 non-vital primary molars in 43 patients aged from four to seven years old were randomly divided into 3 equal groups. In Group I (control group), 2 ml of 1% NaOCl was used for irrigation after each file. In Group II, 5 ml of 0.2% chitosan was used as final irrigat and left in the canal for one minute. While in group III chitosan was left in the canal for 3 minutes. Clinical Assessment was performed regarding pain on percussion and changes in mucobuccal fold. Radiographical evaluation was done at 3,6,12 months follow up intervals using standardized periapical radiographs and analyzed using Image J program. Results: Studied teeth were recorded as first primary molars (D) and second primary molars (E) with total percentage for each group (I, II and III). Although the high clinical and radiographic success rate, there was no significant difference between the three groups. Conclusion: Pulpectomy irrigation using either NaOCl alone or chitosan as a final irrigant for one or three minutes exhibited a good clinical and radiographic success rate with no significance difference.